Open‐Circuit Ultrafast Generation of Nanoscopic Toroidal Moments: The Swift Phase Generator (Adv. Quantum Technol. 1‐2/2019). Issue 1 (13th February 2019) - Wätzel, Jonas; Berakdar, Jamal
Abstract : Few‐cycle terahertz pulses with appropriately shaped polarization trigger a toroidal moment (T) in a neutral donut‐shaped nanostructure. The curl‐free vector‐potential (A) associated with T can be employed to modulate the phase in quantum systems swiftly and free of electric and magnetic fields. Due to its specific symmetry, the generated toroidal moment can excite directly systems with broken time and space inversion symmetry such as toroidally ordered materials. The generation of the toroidal moment and its use are demonstrated by Jonas Wätzel and Jamal Berakdar in article number1800096 .